2016
DOI: 10.1111/ejh.12806
|View full text |Cite
|
Sign up to set email alerts
|

Anagrelide reduces thrombotic risk in essential thrombocythaemia vs. hydroxyurea plus aspirin

Abstract: Anagrelide significantly decreased the number of patients experiencing minor arterial and minor venous TEs versus HU + ASA over 6 yr. Risk of TE after diagnosis was significantly increased if the patient had TE before diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
(39 reference statements)
1
17
0
1
Order By: Relevance
“…It builds on the findings of analyses at 6 years, reporting data at 10 years. Study methods are fully reported elsewhere 14 . In brief, a questionnaire based on the 2008 revision of the World Health Organization (WHO) diagnostic criteria 16 was used to collect data on ET patients electronically.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It builds on the findings of analyses at 6 years, reporting data at 10 years. Study methods are fully reported elsewhere 14 . In brief, a questionnaire based on the 2008 revision of the World Health Organization (WHO) diagnostic criteria 16 was used to collect data on ET patients electronically.…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, we reported a study of ET management using MPN data taken from a registry created by the Hungarian MPN Working Group (HUMYPRON GROUP) 14 . The HUMYPRON GROUP MPN registry includes patient data on epidemiology, diagnostics, therapeutics and disease complications, 14,15 with data entered online enabling continuing update and searches for association analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 141 HU + ASA és a 139 anagrelidkezelt beteg TEeseményeinek az eddigi közleményekkel [9,10] való összehasonlítása érdekes, azoktól jelentősen eltérő eredményt mutat [11].…”
Section: Megbeszélésunclassified
“…was not inferiorly effective in the prevention of thrombotic events in comparison with the unspecific cytoreductive compound hydroxyurea in the ANAHYDRET study which included exclusively WHO-classified patients with ET. 5,6 A retrospective analysis of a large anagrelide-treated thrombocythemic MPN patient cohort suggests that both elevated WBC and elevated PLT counts during follow-up are associated with a statistically significant elevated rate of thrombosis. 7 Otherwise, near to normal values of PLT and WBC counts are associated with the lowest rate of thrombosis, whereas lowering of only one parameter is suboptimal when the other parameter is still elevated.…”
mentioning
confidence: 99%